The use of mentalization-based techniques in online psychodynamic child psychotherapy - Coskun, Aysenur; Halfon, Sibel; Bate, Jordan; Midgley, Nick (Routledge Journals, Taylor & Francis Ltd, 2023)
Objective: Psychodynamic child psychotherapy is an evidence-based approach for a range of child mental health difficulties and needs to constantly adapt to meet the needs of children. This study is the first to investigate whether the use of mentalization-based interventions (i.e., a focus on promoting attention control, emotion regulation, and explicit mentalization) predicted a good therapeutic outcome in online psychodynamic child therapy sessions conducted during the COVID-19 pandemic. Methods: The sample included 51 Turkish children (M-age = 7.43, 49% girls) with mixed emotional and behavioral problems. Independent raters coded 203 sessions from different phases in each child's treatment using the Mentalization-Based Treatment for Children Adherence Scale (MBT-CAS). Results: Multilevel modeling analyses showed children with higher emotional lability benefited more from attention control interventions compared to those with lower emotional lability. Discussion: Interventions that focus on developing the basic building blocks of mentalizing may be effective components of therapeutic action for online delivery of psychodynamic child psychotherapy, especially for children with greater emotional lability.
Keywords: Psychodynamic Child Psychotherapy; Mentalization-Based Techniques; Emotional Lability; Attention Control; Covıd-19 Pandemic; Validity; Therapy; Emotion; Context; Trauma; Health